MULTIPLE PERFORMANCE CHARACTERISTICS OPTIMIZATION OF HARD TURNING OPERATIONS USING UTILITY BASED-TAGUCHI APPROACH (Journal of Mechanical Engineering, 2016)
In order to sustain in the global competitive scenario, the manufacturing industries have beenpracticing the various tools to achieve the high quality products at lower cost. Selection of appropriate cutting conditions is necessary to improve machinabilty of a work piece material. The present work objective is to find out the optimum cutting parameters in turning of hardened AISI M2 steel using cryogenically treated cutting inserts. The Utility concept coupled with Taguchi approach was employed to optimize both surface roughness and power consumption simultaneously. According to Analysis of variance (ANOVA) results, the feed was the major dominant factor followed by the cutting speed on multiple performance characteristics. The necessary optimum conditions for multiple performance characteristics optimization were obtained as cutting speed of 100 m/min, feed 0.04 mm/rev and depth of cut of 0.2 mm.